Phenotype of cytochrome P4501B1 gene (CYP1B1) mutations in Japanese patients with primary congenital glaucoma. Issue 3 (1st March 2003) - Ohtake, Y; Tanino, T; Suzuki, Y; Miyata, H; Taomoto, M; Azuma, N; Tanihara, H; Araie, M; Mashima, Y
Abstract : Aim: To investigate the phenotypes associated with cytochrome P4501B1 gene ( CYP1B1 ) mutations in Japanese patients with primary congenital glaucoma (PCG). Methods: 66 Japanese patients with PCG were screened for sequence mutations in the CYP1B1 gene using single strand conformation polymorphism analysis followed by automated DNA sequencing. 11 cases had a CYP1B1 mutation in both alleles (the mutation group) and 21 cases did not have a CYP1B1 mutation (the "no mutation" group). The clinical features, such as age of onset, sex, intraocular pressure, and Descemet's membrane rupture, of the two groups were compared. Results: The clinical symptoms and signs did not differ for the two groups. The mean age at onset was 1.7 months in the mutation group and 3.1 months in the no mutation group, and the male:female ratio was 6:5 in the mutation group and 19:2 in the no mutation group. Both of these differences were statistically significant. Conclusions: In clinically diagnosed cases of PCG, a subgroup shows a CYP1B1 gene mutation. Age at onset was earlier in PCG patients with CYP1B1 mutations than in patients without mutations. Women were more prevalent among patients with mutations than those without mutations.